Urgensi Layanan Konseling Terhadap Narapidana - Chairunnisa'; Dita Sephira Amalia; M. Alwana Al-Afifi; Rizka Fitriani; Deylant Januar E; Affan Yusra (CV. Multi Kreasi Media, 2022)
“Loss of independence” or the limited rights that prisoners have is one of the stressors that causes their mental illness. The research method that will be used is a literature review of scientific articles in the form of journals that have been collected through the Google search engine and Google Scholar. From these sources, it can be concluded that awareness of the importance of counseling services for prisoners has begun to be seen, where many researches have raised the topic of similar problems. It is hoped that counseling services for prisoners can continue to be developed so that the goals of correctional institutions in improving the quality of community behavior can be realized.